Development of canine biomarker based detection and quantification assays for determining food adulteration and halal authentication / Md. Mahfujur Rahman - Rahman, Md. Mahfujur (2015)
The authentication of food product is an important issue to safeguard consumer rights, religious belief, and health and fair-trade economy. Proper labeling of food products allows consumers to make a well-informed purchase decision, commensurations his religious faith, health requirement and of course his personal budget. “Halal” logo on food products reflects both the ingredients and processing steps of the products confirm the Shariah Principles of Islam for hygienic foods. Since halal foods serve the health and religious requirements, their appeal is huge even to the non-Muslim customers. The huge turnover (US$700 billion/ annum) and expanding demands of halal food products testify their widespread popularity throughout the world. The specialized processing, stringent supply chain and safety standard of halal foods have made them costlier to their non-halal counterparts and consequently halal branded products have been targeted for fraud labeling for years. Dog meat consumption is forbidden in Islam and it has been a less discussed issue for fraudulent mixing in halal foods. However, report has been published for the consumption of dog meats by Vietnamese and Myanmarian workers in Malaysia. Dog meat consumptions are also common in South Korea, China and Vietnam. Additionally, the widespread availability of stray dogs without any offered prices in many countries has made it as a highly potential adulterant in halal foods. In literature, five polymerase chain reactions (PCR) assays have been proposed for the detection of dog meats. However, most of the documented assays have targeted longer DNA fragment (≥213 bp) and none of them have tested under complex food matrices. Longer DNA fragments frequently break down during food processing, causing false negative detection in the final assay. To overcome the potential limitations of the existing assays, we have developed short DNA fragment based conventional PCR, PCR-RFLP and real-time PCR assays targeting a 100-bp site of mitochondrial cytochrome b gene. The specificity of the assays were tested using DNA extracted from dog and common meat providing land, aquatic, bird and plant species. The assay stability was tested under different food processing conditions, including boiling, autoclaving and oven heating under pure, admixed and commercial food matrices and was found to be highly stable. The developed conventional PCR assay successfully detected 0.1% to 0.2% (w/w) canine meat from admixed and commercial samples, reflecting its stability and sensitivity under complex matrices. PCR products were authenticated by digesting the product with AluI restriction enzyme which generated 51-, 30- and 19-bp fragments. The digested fragments were successfully separated using Experion Bioanalyzer kit. The sensitivity of the PCR-RFLP assay was 0.0001-ng canine DNA under pure and 0.01% (w/w) canine meat spiked in chicken and beef burger formulations. Finally, a TaqMan probe real-time PCR assay was developed and it was found highly stable and sensitive both under pure and complex matrices. The developed real time-PCR assay successfully detected 0.01% (w/w, 0.002 ng DNA) canine meat spiked in commercial chicken nuggets. A total of six halal branded food products obtained from different Malaysian outlets were screen and no canine adulteration was detected.